2008
DOI: 10.1136/thx.2007.090803
|View full text |Cite
|
Sign up to set email alerts
|

Association between asthma and serum adiponectin concentration in women

Abstract: Background: The association of murine asthma with adiposity may be mediated by adiponectin, an antiinflammatory adipokine with reduced serum concentrations in obese subjects. A study was undertaken to examine whether the serum adiponectin concentration is associated with human asthma and whether it explains the association between adiposity and asthma, particularly in women and in premenopausal women. Methods: A cross-sectional analysis was performed of 2890 eligible subjects at year 15 of the Coronary Artery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
114
2
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 134 publications
(129 citation statements)
references
References 32 publications
(34 reference statements)
7
114
2
6
Order By: Relevance
“…findings of our longitudinal study suggest a clear direction to our previously described cross-sectional association between serum adiponectin and asthma among women (6). Although serum adiponectin concentrations and BMI are inversely correlated with each other (r of 20.33; P , 0.001), we found that low values of the former may be more important than high values of the latter in predicting the risk for incident asthma among female current smokers.…”
Section: Discussionsupporting
confidence: 69%
See 4 more Smart Citations
“…findings of our longitudinal study suggest a clear direction to our previously described cross-sectional association between serum adiponectin and asthma among women (6). Although serum adiponectin concentrations and BMI are inversely correlated with each other (r of 20.33; P , 0.001), we found that low values of the former may be more important than high values of the latter in predicting the risk for incident asthma among female current smokers.…”
Section: Discussionsupporting
confidence: 69%
“…The strengths of our study include its focus on women, welldefined study population set within a cohort structure, and its clinical translational character, based on the recently published data on the role of systemic adiponectin in mouse and human asthma (6,22,37). Further, the results from our longitudinal analyses are supported by our previous cross-sectional analyses (6).…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations